Pemetaan Kriteria Homestay di Desa Wisata Banyuwangi Melalui Penerapan ASEAN Homestay Standard - Reni Nur Jannah; Wijaya, Jemi Cahya Adi; Octanisa, Dheanita Sekarini; Handoko, Rudi Tri (JURNAL BISNIS HOSPITALITI, 2025)
Homestay is an accommodation business that offers rooms provided by local residents for guests in a certain period of time. By offering a different lodging atmosphere, there are nine criteria recommended by the ASEAN organization as a standardization of the homestay concept. The development of homestay businesses is intensively carried out by the Banyuwangi Regency Government spread throughout tourist villages, but there is a perception that the homestay concept implemented does not meet standards. This study aims to explore the characteristics of homestays spread across Banyuwangi Regency Tourism Villages through the application of the ASEAN Homestay Standard criteria. Through a self-assessment method summarized in 88 statements representing the nine criteria as indicators, homestay owners filled out a questionnaire with a Guttman scale approach. Then, the data were analyzed using SPSS and Excel statistics. The results showed that the level of implementation of the nine ASEAN homestay standard criteria was 83% which was interpreted as having been implemented very well. However, in the "activity" criterion, the implementation of ASEAN homestay standards must be further improved because it has the highest importance weight. This research is expected to contribute ideas and knowledge in the development of science, especially in the field of Homestay Management